Pelestarian budaya lokal sebagai upaya mempertahankan identitas nasional - rahmadani, nabila rizky (Maliki Interdisciplinary Journal, 2026)
Indonesia is a multicultural country with a diversity of ethnic groups, languages, and cultures that constitute both its wealth and its national identity. However, in this era of globalization, local cultures face the threat of extinction due to a lack of public awareness, shifts in the lifestyles of younger generations who are more interested in foreign trends, and the loss of character values such as mutual cooperation and regional languages. This article discusses how the preservation of local culture is vital to maintaining national identity. Everyone has a duty to preserve local culture as an effort to safeguard cultural values so they are not lost to the passage of time. One approach that can be taken is through the use of technology. By strengthening cultural identity through the utilization of technology, the values of Pancasila can be implemented to realize the nation’s aspirations and maintain unity amidst diversity.